A Study of Lifelong Education for Persons with Intellectual Disabilities at the University Level - Maebara, Kazuaki; Fujii, Yoshihiro; Tanimura, Kazunori; Suzuki, Toru; Takeda, Atsushi (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: In recent years, there has been growing interest in developing lifelong education for persons with disabilities at universities and other institutions of higher learning. However, there is still a lack of practical research on people with intellectual disabilities who participate in lifelong education. Objective: This study analyzes the experiences of participants with intellectual disabilities obtained from the practice of the Lifelong Education Program for Persons with Disabilities (AULEPP). It discusses perspectives for the future development of lifelong education. Methods: Eleven persons with intellectual disabilities who participated in the AULEPP from October 2021 to February 2022 were included in the study. Three surveys were administered to these participants before and after the AULEPP and for each lecture. Results: The average number of participants in each lecture was 5.2, and four participants attended more than eight lectures. Qualitative analysis of the survey results revealed that participants acquired new knowledge, expressed the need for continuous learning, and proposed new questions. The lectures helped them recognize changes in their perspectives on daily life and society. Most of the lectures were conducted online, but there were no negative comments about this modality. Conclusions: The study revealed the need to create opportunities for participants to find meaning in lectures, the effectiveness of online media, and the role of lifelong college education in the community. It is necessary to investigate the transferability of these results to urban areas and explore outcome measures and program content to build an evidence-based lifelong learning program.